2020
DOI: 10.1101/2020.12.01.20241281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting the shared genetic architecture of suicide attempt, psychiatric disorders and known risk factors

Abstract: Suicide is a leading cause of death worldwide and non-fatal suicide attempts, which occur far more frequently, are a major source of disability and social and economic burden. Both are known to have a substantial genetic etiology, which is partially shared and partially distinct from that of related psychiatric disorders. We conducted a genome-wide association study (GWAS) of 29,782 suicide attempt (SA) cases and 519,961 controls in the International Suicide Genetics Consortium and conditioned the results on p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 79 publications
3
11
0
Order By: Relevance
“…This is consistent with phenotypic correlations and with other genetically informed studies. For instance, Lim et al [42] found that a PGS for MDD was the most robust predictor of self-harm in the UK Biobank, while a recent GWAS of suicide attempt reported a genetic correlation of r g = 0.78 (SE = 0.03) with MDD [19]. The PGS for risky behaviors was also significantly associated with all 4 self-harm measures, although it explained considerably less variance in all 4 phenotypes (<1%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with phenotypic correlations and with other genetically informed studies. For instance, Lim et al [42] found that a PGS for MDD was the most robust predictor of self-harm in the UK Biobank, while a recent GWAS of suicide attempt reported a genetic correlation of r g = 0.78 (SE = 0.03) with MDD [19]. The PGS for risky behaviors was also significantly associated with all 4 self-harm measures, although it explained considerably less variance in all 4 phenotypes (<1%).…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal ideation, attempts, and NSSI are moderately heritable according to twin and family studies (h 2 ∼ 17-59%) [9,13], and shared genetic factors contribute to the covariance between STBs and NSSI [9,14]. Recent genome-wide association studies (GWAS) of self-harm, more broadly [15], and specifically of STB [16][17][18][19], have identified genome-wide significant loci, and subsequent polygenic risk scores of these measures have been found to predict modest variance in self-harm behaviors in independent samples. These studies estimate the genomewide SNP heritability of self-harming behaviors to be 7-10% and also estimate high genetic correlations between self-harming behaviors and MDD (r g ∼ 0.8) as well as other psychiatric disorders [15][16][17]19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important consideration in such analyses is the role of MDD -suicidal thoughts and behaviors are among diagnostic criteria for MDD, even though they are pervasive in other psychiatric syndromes (American Psychiatric Association, 2013). Among psychiatric disorders, depression shares one of the highest genetic correlations with both suicide attempt (Mullins et al, 2020;Ruderfer et al, 2020) and SUDs (Abdellaoui et al, 2021), yet whether the genetic relationship between SUDs and suicide-related behaviors extends beyond depression remains understudied. For instance, Mullins et al (preprint; estimated genetic correlations with suicide attempt before and after conditioning suicide attempt on MDD.…”
Section: Introductionmentioning
confidence: 99%
“…However, in another study, alcohol use and suicide attempt were found only to be related through their common associations with depression (Grazioli et al, 2018). In addition to MDD, risk-taking behaviors are also correlated with both SUDs (Johnson et al, 2020; Zhou, Sealock, et al, 2020) and suicide attempt (Mullins et al, 2020), and could be contributing to observed genetic correlations among these traits. Deeper phenotyping of lethality of suicide attempts have revealed a role for impulsivity, albeit mixed (Baca-Garcia et al, 2005) and the role of risk-taking as a genetic co-contributor to SUD and suicide remains unknown.…”
Section: Introductionmentioning
confidence: 99%